Pencegahan Fraud Melalui Sharia Compliance dan Islamic Corporate Governance pada Bank Syariah Indonesia - Eko Cahyo Mayndarto (ITB AAS INDONESIA Surakarta, 2023)
This research is motivated by the importance of fraud prevention at Indonesian Sharia Banks. This study aims to identify and analyze Fraud Prevention through Sharia Compliance and Islamic Corporate Governance at Indonesian Sharia Banks. This research is a descriptive research with a quantitative approach. The sample in this study were 100 employees of Bank Syariah Indonesia which were taken by random sampling. Data collection techniques by way of observation, questionnaires and questionnaires. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression with SPSS tools. The results of this study indicate that 1) Sharia Compliance has a positive and significant effect on fraud prevention at Bank Syariah Indonesia, 2) Islamic Corporate Governance has a positive and significant effect on fraud prevention at Bank Syariah Indonesia, and 3) Sharia Compilance and Islamic Corporate Governance together the same positive and significant effect on fraud prevention at Bank Syariah Indonesia. The findings of this study reveal that if Bank Syariah Indonesia wants to improve fraud prevention, it must increase sharia compliance and Islamic corporate governance